Counter-current fractionation-assisted and bioassay-guided separation of active compounds from cranberry and their interaction with α-glucosidase. (June 2021) - Xue, Hongkun; Tan, Jiaqi; Zhu, Xiaohan; Li, Qian; Tang, Jintian; Cai, Xu
Abstract: An effective method for the selection of active compounds from cranberry based on counter-current fractionation and bioassay-guided separation was established. Cranberry extract showed potential α-glucosidase inhibitory activity. The active compounds were extracted by different solvents and enriched in water. The water extract was divided into eight fractions via high-speed counter-current chromatography to further track the active compounds. Results indicated that the α-glucosidase inhibitory activity of F7 was remarkable higher than the other fractions. Four compounds, including delphinidin-3-glucoside (D3G), cyanidin-3-glucoside, cyanidin-3-rutinoside, and pelargonidin-3-glucoside, were separated from F7 through column chromatography, and their structures were identified by high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry, 1H nuclear magnetic resonance (NMR), and 13C NMR. D3G showed the strongest α-glucosidase inhibitory activity among the compounds. Moreover, the interaction mechanism between α-glucosidase and D3G was clearly characterized and described by spectroscopic analyses and molecular docking. D3G could spontaneously bind with α-glucosidase to form complexes through hydrophobic interaction. The secondary structure of α-glucosidase changed in varying degrees after complexation with D3G. The α-helix and β-turn contents of α-glucosidase markedly decreased, whereas the irregular coil increased. These findings provide a new insight into the interaction between α-glucosidase and D3G. Highlights: Counter-current fractionation assisted bioassay-guided separation. Four compoundswere separated from cranberry. Delphinidin-3-glucoside (D3G) showed the strongest α-glucosidase inhibitory activity. Interaction between α-glucosidase and D3G was studied. Spectroscopy and molecular docking explored the interaction mechanism.